PERANCANGAN APLIKASI SIMULASI METODE HAVERSINE DALAM PENCARIAN LOKASI PKL TERDEKAT UNTUK SISWA/I SMKS MUSTAFA PERBAUNGAN - PRASETIO, ANNAS (STMIK KAPUTAMA, 2021)
To get a skill is not only obtained from school but obtained from the PKL (Field Work Practice). One of the schools that requires students to have skills in the field of communication and information technology is SMKS Mustafa Perbaungan. Mustafa Perbaungan Vocational High School is located in Perbaungan District, Hamlet V, Lidah Tanah Village, Serdang Bedagai Regency. There are several street vendors in Perbaungan District which are estimated based on the distance from the school, such as the BRI BANK, POS Office, Social Service, Sub-District Office, Youth and Sports Service and so on. This research is deemed necessary to determine the application of the haversine method in finding the nearest street vendors location for students of SMKS Mustafa Perbaungan. The results of this study found that the closest order is the Camat Office, Perbaungan POS Office, BRI BANK, Social Service, and Youth and Sports Office.